The problems of physics - Leggett, A. J. (Anthony J.); Oxford eBooks (Oxford : Oxford University Press, 1987)
This book aims to give the non-specialist reader a general overview of what physicists think they do and do not know in some representative frontier areas of contemporary physics. It focuses on the fundamental problems at the heart of the subject, and emphasizes the provisional nature of our present understanding of things.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Physics; Particles (Nuclear physics); Condensed matter; Cosmology; Electronic books